The clinicopathologic characteristics and prognostic factors of gastroesophageal junction tumors according to Siewert classification - Öven Ustaalioğlu, Bala Başak; Tilki, Metin; Sümelioğlu, Ali; Bilici, Ahmet; Gönen, Can; Ustaalioğlu, Recep; Balvan, Özlem; Aliustaoğlu, Mehmet (AVES, 2017)
Objective: The treatment of gastroesophageal junction tumors remains controversial due to confusion on whether they should be considered as primary esophageal or as gastric tumors. The incidence of these tumors with poor prognosis has increased, thus creating scientific interest on gastroesophageal cancers. Esophagogastric cancers are classified according to their location by Siewert, and the treatment of each type varies. We evaluated the prognostic factors and differences in clinicopathologic factors of patients with gastroesophageal junction tumor, who have been treated and followed-up in our clinics. Material and Methods: We retrospectively analyzed 187 patients with gastroesophageal junction tumors who have been operated and treated in the Oncology Department between 2005 and 2014. The chi-square test was used to evaluate differences in clinicopathologic factors among Siewert groups I, II and III. Prognostic factors were analyzed by univariate and multivariate analysis. Results: The median age of our patients was 62 years, and approximately 70% was male. Nineteen patients (10.2%) had Siewert I tumors, 40 (21.4%) II, and the remaining 128 (64.4%) had Siewert III tumors. Siewert III tumors were at more advanced pathologic and T stages. Preoperative chemoradiotherapy was mostly applied to Siewert group I patients. There was no difference between the 3 groups in terms of recurrence. While the median overall survival and 2-year overall survival rate were 26.6 months and 39.6%, the median disease free survival and disease free survival rates were 16.5 months and 30.1%, respectively. The N stage, pathologic stage, vascular invasion, lymphatic invasion, perineural invasion, surgical margin, and grade were associated with both overall survival and disease free survival, while pathologic stage and presence of recurrence were significant factors for overall survival. The median disease free survival for Siewert III tumors was 20 months, 11.3 month for Siewert I tumors, and 14 months for Siewert II tumors, but the finding was not statistically significant (p= 0.08). Conclusion: Although gastroesophageal junction tumors were grouped according to their location and they exerted different clinicopathologic properties, their prognosis was similar.
WOS: 000396634600006
PubMed ID: 28589183
Keywords: Esophagogastric Junction; Siewert Classification; Prognosis